The Role of Emotional Expression in Fluent Speech Production for ESL and EFL Learners (Yangi O'zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2024)
Fluent speech production in English as a Second Language (ESL) and English as a Foreign Language (EFL) contexts involves not only linguistic competence but also emotional expression. This article explores the role of emotional expression in enhancing fluent speech production among ESL and EFL learners. Drawing on theories from linguistics and educational psychology, the article discusses how emotional engagement influences language acquisition and communicative competence. Strategies for integrating emotional expression into language teaching practices are examined, highlighting the importance of creating supportive learning environments that foster emotional engagement and linguistic fluency.